Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The function $f(x) = 1-f(x-1)$, for positive interger, $x$. If $f(2) = 12$, compute $ f(2012)$

share|improve this question
add comment

3 Answers

up vote 7 down vote accepted

$f(x)=1-f(x-1)=1-(1-f(x-2))=f(x-2)=...=f(2)$ is $x$ is even

So, $f(2012)=f(2)=12$

If x is odd, $f(x)$ will reduce to $f(1)=1-f(2)=1-12=-11$

share|improve this answer
    
So, the answer to f(2) and f(2012) are both 12? And any even number is also 12? –  Ctrl Sep 9 '12 at 17:48
    
Yes, to me that is the case. –  lab bhattacharjee Sep 10 '12 at 4:59
add comment

Since $x$ is an integer, I will replace it with $k$. Also, instead of $f (x)$ I will use $x_k$. Hence, the rephrased problem is the following:

Problem: for nonnegative $k$ we have that $x_{k+1} = 1 - x_k$. If $x_2 = 12$, compute $x_{2012}$.

Consider the discrete-time dynamical system

$$x_{k+1} = a x_k + b$$

where $a, b \in \mathbb{R}$. It is easy to show that for all $k \geq 0$ we have that

$$x_k = a^k x_0 + \displaystyle\sum_{i=0}^{k-1} a^i b = a^k x_0 + \displaystyle \left(\frac{1 - a^k}{1 - a}\right) b$$

Let's make $a = -1$ and $b = 1$. We then have that the general solution of $x_{k+1} = 1- x_k$ is

$$x_k = (-1)^k x_0 + \displaystyle \left(\frac{1 - (-1)^k}{2}\right)$$

If $x_2 = 12$, then $x_0 = 12$ as well. Note that $x_{2012} = (-1)^{2012} x_0 = x_0 = 12$. I do concede that this approach is total overkill, but next time you see something of the form $x_{k+1} = a x_k + b$, you know what to do.

share|improve this answer
    
Nice one! ${}{}$ –  Pedro Tamaroff Sep 8 '12 at 17:33
add comment

Hint $\ $ Iterating a function $\rm\:g\:$ of period $\rm\,n\:$ produces a sequence of period $\rm\,n$

$$\rm g^n = Id,\,\ f(k\!+\!1) = g\,f(k)\ \Rightarrow\ f(k\!+\!n) = g^n f(k) = f(k)\ \Rightarrow\ f(k\!+\!jn) = f(k) $$

Yours is the special case $\rm\:n=2,\:$ since $\rm\:f(k\!+\!1) = 1-f(k) = g\,f(k),\:$ for $\rm\:g(x) = 1\!-\!x,\:$ where $\rm\:g^2(x) = g(g(x)) = g(1\!-\!x) = 1\!-\!(1\!-\!x) = x,\ $ so $\rm\:g^2(x) = x,\:$ i.e. $\rm\ g^2 = Id.$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.